Effect of Home-Based Cardiac Rehabilitation Quality of Life in the Patients with Myocardical Infarction - Farahnaz Mohammadi; Akram Taherian; Mohammad Ali Hosseini; Mehdi Rahgozar (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: The aim of the present study was to determine the effects of home based cardiac rehabilitation programs (CRP) on quality of life in post Myocardial Infarction (MI) patients. Materials & Methods: We conducted a quasi experimental design study with a non randomized sampling, pretest - posttest control group. After matching, 38 subjects were allocated randomized either a home based CRP (n=18) and a control group (n=20). At the base line knowledge about disease management and quality of life (QOL) were measured .Then experimental group were instructed by multidisciplinary team about home based CRP. The patients received an instructional booklet containing the above mentioned information and also received support and guidance through phone call and home visits, on the other hand, disease management and health behavior were been measured in ever home visiting. At the end of three months follow up, patient's knowledge and QOL were measured again. Results: The research findings indicated the improvement QOL for the Experimental group following the application of home-based CRP, this improvement included all dimensions such as physical, mental, and psychological ones (P = 0.000). No significant improvement was observed in social dimension of QOL following the experimental group (P=0.308). For control group, the reduction of averages in different dimensions of QOLwas noticeable. However, this reduction was noticeable and just meaningful in social dimension (P=0.009). Comparing groups, before the intervention, indicated that there weren't significant differences in different dimensions of QOL but, after the intervention, there was significant difference just in psychological dimension (P=0.032). Conclusion: Significant positive changes in physical, psychological dimensions and whole of QOL indicated positive effect on homebased CRP on QOL in experimental group. Although there was just significant difference between groups in psychological demands of QOL after the treatment, but research hypothesis, "positive effect of homebased CRP on QOL" wasn't supported. It may be due to the fact that QOL is a subjective, dynamic and multidimensional concept and defensible outcomes need using larger sample with longer period of time especially based on team approach.